2018
DOI: 10.1149/2.0301811jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Quantitative Analysis of Consumption of Fluoroethylene Carbonate Additives on Silicon Alloy Anodes

Abstract: Fluoroethylene carbonate (FEC) is known to be an effective electrolyte additive in silicon-based anodes for lithium ion batteries, but reported to be consumed, eventually resulting in a sudden capacity fade. We quantified the amount of remaining FEC in separators harvested from the cycled cells using infrared (IR) spectroscopy. FEC is linearly depleted over cycles until complete consumption. When the amount of FEC additive is nearly zero, capacity of the cell suddenly drops. It is first shown that IR spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In these systems, complete consumption of FEC is marked by a distinct drop in capacity retention. [27,36,37] However, from a material testing perspective, excess electrolyte volumes "turn off" some of the undesired side reactions described above and therefore allow the investigation of other degradation phenomena. [38,39] Lastly, insufficient drying of cell components (electrodes, separators or coin cell parts) or high moisture levels within the electrolyte can lead to electrolyte and electrolyte salt decomposition reactions (e. g., electrolytes containing LiPF 6 as conducting salt), resulting in aging effects.…”
Section: Other Considerations For Cell Manufacturingmentioning
confidence: 99%
“…In these systems, complete consumption of FEC is marked by a distinct drop in capacity retention. [27,36,37] However, from a material testing perspective, excess electrolyte volumes "turn off" some of the undesired side reactions described above and therefore allow the investigation of other degradation phenomena. [38,39] Lastly, insufficient drying of cell components (electrodes, separators or coin cell parts) or high moisture levels within the electrolyte can lead to electrolyte and electrolyte salt decomposition reactions (e. g., electrolytes containing LiPF 6 as conducting salt), resulting in aging effects.…”
Section: Other Considerations For Cell Manufacturingmentioning
confidence: 99%
“…It is also crucial to emphasize the relevance that the studies on electrolyte additives have contributed to improving battery performances. It was demonstrated that the use of carbonate-based additives helps to achieve a better quality SEI with an improved coulombic efficiency and a long cycling life [31][32][33][34][35][36]. Furthermore, plenty of research has been addressed on binder materials in which the function is to give a stronger adhesion to avoid electrical disconnection between the particles and the current collector.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it seems that, among the various radiolysis processes for FEC decomposition considered in the literature, 39 the one going through the F loss radical should be the most prevalent under our conditions as no IR band at 1835 cm −1 can be detected in the spectra of Figure 3b. Such a band is quite specific of FEC, 40 and its absence indicates that F-substituted cyclic units are not detectable in the formed polymer.…”
Section: Resultsmentioning
confidence: 99%